2022
DOI: 10.1177/01605976221107093
|View full text |Cite
|
Sign up to set email alerts
|

Building Peace in Northern Ireland: Hopes for the Future

Abstract: Since the Good Friday Agreement of 1998, over 2 billion Euros have been poured into Northern Ireland for peacebuilding. This article presents the hopes and experiences of workers in CSOs funded by either or both funds, development officers, and civil servants employed by the funders. They confirm that peacebuilding and reconciliation projects funded by the European Union (EU) Peace and Reconciliation Fund and the International Fund for Ireland (IFI) have positively contributed to the peace process in Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, at this time of writing, the DUP continues to reject the Framework and refuses to participate in the powersharing executive at Stormont. Thus, the peace is not sacrosanct as Northern Ireland continues to experience ongoing political tensions contributed by Brexit including disputes over culture and identity politics, the exclusion of marginalized communities, the COVID-19 pandemic, and the challenges of reconciliation and the Border poll that have estranged working class Loyalists and the DUP over the potential reunification of the island as a result of the Brexit fiasco (Byrne et al 2022). For example, a recent LucidTalk polling for the Belfast Telegraph found that the majority of PUL participants would vote against the 1998 B/GFA today clearly highlighting the fragility of Northern Ireland's peace process (Breen 2023).…”
Section: A Cold and Frosty Peace By Piecesmentioning
confidence: 99%
“…However, at this time of writing, the DUP continues to reject the Framework and refuses to participate in the powersharing executive at Stormont. Thus, the peace is not sacrosanct as Northern Ireland continues to experience ongoing political tensions contributed by Brexit including disputes over culture and identity politics, the exclusion of marginalized communities, the COVID-19 pandemic, and the challenges of reconciliation and the Border poll that have estranged working class Loyalists and the DUP over the potential reunification of the island as a result of the Brexit fiasco (Byrne et al 2022). For example, a recent LucidTalk polling for the Belfast Telegraph found that the majority of PUL participants would vote against the 1998 B/GFA today clearly highlighting the fragility of Northern Ireland's peace process (Breen 2023).…”
Section: A Cold and Frosty Peace By Piecesmentioning
confidence: 99%